IMPLEMENTASI KEBIJAKAN DESENTRALISASI DALAM MENINGKATKAN EFEKTIVITAS PEMERINTAHAN DAERAH DI INDONESIA - Wahyuni, Made Dewi; Rimbawan, I Putu Dedy; Awak, Evilia Vanesa (Universitas Mahendradatta Denpasar, 2024)
This research aims to analyze the implementation of decentralization policies in Indonesia and their impact on the effectiveness of regional government. This study uses a qualitative approach with case study methods in several areas. Data was collected through observation and document analysis. The research results show that decentralization has increased community participation and regional government responsiveness, although there are still obstacles such as human resource capacity and budget management. This research provides recommendations for improving the implementation of decentralization policies in order to increase the effectiveness of regional government.